Uso do modelo celular tridimensional de adenocarcinoma de câncer de pulmão na triagem de compostos organocalcogênios - Batista, Jéssica Eduarda dos Santos (2019)
Pulmonary adenocarcinoma is one of the leading causes of death in the world associated with cancer, but eradication or control of this disease is not possible yet. Treatment with chemotherapeutic drugs such as cisplatin has been successful, leading to increased survival of some patients. Its mode of action occurs through direct binding to DNA preventing replication, leading to cell death. However, the development of cisplatin resistance represents a serious clinical problem. Studies focusing on new molecules that are more effective in treating cancer have gained notoriety, such as the antitumor properties of organocalcogen compounds that are used in organic syntheses. The identification of compounds with therapeutic potential is usually initiated in in vitro studies, as it allows the study of human cells in a larger number of combinations, with different parameters. Nevertheless, monolayer (2D) cell culture does not reproduce the spatial complexity of neoplastic cells, thus does not allow the same interactions between cellular and extracellular environments, for example. Thus, there is great interest in cellular models that reproduce more accurate pathophysiological in vitro characteristics found in vivo, such as three-dimensional cultivation. Three-dimensional cultures (spheroids) allow cells to perform cell-cell or cell-matrix interactions. These interactions lead to increased cell differentiation, activate cell signaling due to extracellular matrix components, modify the gene expression pattern previously observed in 2D culture, and alter the expression of molecules involved in matrix and cell-cell adhesion. In three-dimensional culture the cells are arranged in several layers giving a biological barrier to drug diffusion, which will have to diffuse between these layers, similar to what happens in vivo. In cancer, this culture has been widely used, for example, in research that tests drug efficiency. Thus, the general objective of this work was to develop a three-dimensional cellular model using a lung adenocarcinoma lineage and to use this model to screen for molecules with antitumor potential. Protocols were first tested using either matrigel or agarose gel for spheroid formation. After establishment, the morphometric parameters were evaluated by image analysis and the quantified area. In addition, spheroids were treated with nine organocalcogen compounds and compared with cisplatin chemotherapy, cytotoxicity was evaluated by the mtt assay, all compounds and cisplatin were diluted in DMSO. In this study, we made spheroid formation reliable using an A549 human adenocarcinoma cell line only in the tested agarose gel protocol. All compounds and cisplatin significantly decreased cell viability when compared with the control group after 48 hours. Compound 3 had the lowest IC50 value among all compounds tested after 48h exposure. Considering the data presented here, we demonstrate that a three-dimensional adenocarcinoma model is suitable for screening for possible antitumor agents.